COMPUTER TOMOGRAPHY IMAGING FEATURES OF TUMORS AND SUSPECTED NODAL METASTASES IN HYPOPHARYNGEAL CANCER - Phùng, Thị Hòa; Lương, Thị Minh Hương; Cung, Thanh Tuyền (Tạp chí Tai Mũi Họng Việt Nam, 2025)
Hypopharyngeal cancer is a malignant tumor derived from the malpigi-covered epithelium of the hypopharynx, accounting for 5% of all head and neck cancers, neck ganglion metastasis is a poor prognosis. Objective: To charaterize the the tumor and cervical nodal of patients with hypopharyngeal cancer on a computed tomography scan. Subjects and research methods: Describe a series of cases, including 40 patients are diagnosised hypopharyngeal cancer and treated at K3 Tan Trieu hospital in 2024-2025. Results and discusion: On CT imaging, a hypopharyngeal tissue mass was identified in all patients (100%), increase density (95%), strong drug absorption (92%,) unknown boundaries(97.5%), and heterogeneous density was present in 100% of lesions. The piriform sinus is the most common (82.5%), with the majority of large tumors occupying the entire piriform sinus (40%). Cervical ganglion metastases on CLVT include irregular drug penetration characteristics (100%), loss of umbilical node structure (86.7%), central necrosis (86.7%), the ratio of longitudinal/transverse diameter < 2 accounts for 96.5%, the diameter of the transverse node axis > 1cm accounts for 48.3%. Group II and III Lymph nodes metastasize the most (64.3%). At the time of diagnosis, 72.5% of cases had suspected metastases, including 25% classified as N2b Stage.